THE STUDY OF ATPASE ACTIVITY IN ERYTHROCYTE MEMBRANE OF DIABETES MELLITUS-TYPE 2 SUBJECTS - DR. U. N. SINGH; DR. SUBODH KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Diabetes Mellitus type-2, one of the most prevalent diseases in developing world, is a metabolic disease characterized by hyperglycemia and change in rheological properties. In type-2 Diabetes, there are many biochemical abnormalities in the plasma membrane of erythrocyte including change in ATPase activity. The study includes OPD patients of type-2 Diabetes along with control subjects. In all study subjects, blood samples were analyzed for fasting blood sugar (FBS) & ATPase activity. It was observed in the study that there is decreased Na+- K+ ATPase and increased Mg+ ATPase activity in erythrocyte membrane of diabetic patients and have a negative correlation with fasting blood sugar irrespective of the level of glycemic control in all diabetic patients. The study concluded that change in ATPase activity is one of the biochemical changes in erythrocyte cell membrane in patients of Diabetes Mellitus Type-2.